2010
DOI: 10.1051/0004-6361/200913421
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Milne-Eddington inversions to high spatial resolution observations of the quiet Sun

Abstract: Context. The physical conditions of the solar photosphere change on very small spatial scales both horizontally and vertically. Such a complexity may pose a serious obstacle to the accurate determination of solar magnetic fields. Aims. We examine the applicability of Milne-Eddington (ME) inversions to high spatial resolution observations of the quiet Sun. Our aim is to understand the connection between the ME inferences and the actual stratifications of the atmospheric parameters. Methods. We use magnetoconvec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Since we obtained similar distributions and trends with the two methods, in the following we only present results obtained for average magnetic-field strengths. Note that Orozco Suárez et al (2010) showed that Milne Eddington inversions statistically provide reliable estimates of magnetic-field properties at τ 500 = 0.1, therefore the magnetic-field strength values computed over B0 maps are good representations of results obtained from inversions.…”
Section: Mhd Simulations and Data Analysismentioning
confidence: 91%
“…Since we obtained similar distributions and trends with the two methods, in the following we only present results obtained for average magnetic-field strengths. Note that Orozco Suárez et al (2010) showed that Milne Eddington inversions statistically provide reliable estimates of magnetic-field properties at τ 500 = 0.1, therefore the magnetic-field strength values computed over B0 maps are good representations of results obtained from inversions.…”
Section: Mhd Simulations and Data Analysismentioning
confidence: 91%
“…1 show a map of the vertical field component at continuum optical depth τ 630 = 0.1 directly from the simulation (left panel) in comparison with the map of B LOS from the inversion of the synthetic Stokes profiles (right panel). Orozco Suárez et al (2010) showed that Milne-Eddington inversions fairly well represent the conditions in the atmospheric layers around the τ 630 = 0.1 level. The maps indicate that the morphology of the magnetic structures is well preserved in the maps of B LOS , albeit somewhat smeared owing to instrumental image degradation.…”
Section: Synthetic Observationsmentioning
confidence: 98%
“…On the other hand, the simplifying assumptions of the ME approximation (no gradients of the parameters along the LOS) often raise questions about the validity of the results. Although this is a topic that is constantly under examination, it is generally accepted that the Milne-Eddington approximation gives fair estimates over the range of formation of the line used (Westendorp Plaza et al 1998) and this is not only the case at active regions, but also at finer magnetic concentrations, as has been demonstrated by Orozco Suárez et al (2010). In this study, a crosscomparison with MHD simulations has shown that the magnetic field flux for the Fe I lines closely matches the simulated flux at log τ = −1.…”
Section: Observationsmentioning
confidence: 95%